PHILOSOPHY OF EDUCATION AND THE STATUS OF THE WOMAN IN SOCIETY OF THE XVIII CENTURY - Olha P. Vlasova; Nataliia P. Kostyuk (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose. The objective of this paper is to illustrate how the biological basis of the “natural” male and female characteristics is subjected to doubt in the books of the women-writers - “feminists before feminism” despite the dictatorship of the specific gender norms of the philosophical concepts of that period. These very concepts of the classical philosophy determined ideology, psychology and reasoning of both sexes in the Enlightenment including both public and private spheres. The “picture” of the sociocultural realia of that period is analyzed with the help of the gender which is used here not only as a role or feature but as methodology. The scientific novelty lies in constructing a more complete polyphonical picture of the sociocultural life in the epoch of the Enlightenment in rejecting the “one-sex” interpretation of the philosophy and culture of that period in assuring that there were two subjects in the Enlightenment history and culture-representatives of both sexes. The analysis of philosophical texts and fiction allows to make a conclusion: early feminists were sure that the rational capabilities of men and women do not differ the sexual differences are irrelevant in the problems of intellectual and moral education.